Hak Kawin Muda dalam Islam Sebuah Refleksi KH. Husein Muhammad - Faisol Rizal (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2020)
Marriage at a young age is a phenomenon in some Indonesian society, especially in rural areas or traditional societies, although this kind of marriage is rarely known because it is closed. This fact is due to several reasons which make this young marriage sustainable; including economic, social and cultural factors. In cultural factors, people often associate with elements of religion or the understanding held by society. The problem that arises is that there is no benefit that is obtained if underage marriages are still carried out. The methods used in this article is a qualitative approach to the library, where the focus is aimed against any reference about the religion, culture and islamic boarding school. The approach used is qualitative, which is a research procedure that describes the behavior of certain people, events, or places in detail and depth. While this type of research is literature. Namely, research that relies on reading sources, texts, and various information in the form of reading. In a different reference library research is research that is done to solve a problem that is based on a critical study of library materials and related research results presented in new ways.